Ecological memory of recurrent drought modifies soil processes via changes in soil microbial community - Alberto Canarini (Nature Portfolio, 2021)
Legacies of past ecological disturbances are expected but challenging to demonstrate. Here the authors report a 10-year field experiment in a mountain grassland that shows ecological memory of soil microbial community and functioning in response to recurrent drought.